Sledges of the Norwegian-British-Swedish Antarctic Expedition, 1949–1952 - Reece, Alan (Polar Record, 1953)
Two designs of Nansen-type dog sledge were used by the expedition: a Norwegian design, supplied by A/S Kolbjorn Knutsen and Co. (see Fig. I), and a British design supplied by Airwork General Trading Co. Ltd. After certain modifications and additions, the Norwegian sledge (S.P.R.I. No. 52/11/1) proved much superior to the British sledge.